Optimizing equipment requirements and configuration rules for elderly home treatment environments: a rough set analysis framework - Wang, Rui; Ding, Wei-Yan; Zhou, Zhan-Yan; Li, Xiao-Cheng; Zhang, Yi-Fan (Frontiers in Medicine, 2025)
BackgroundWith the acceleration of global population aging, elderly individuals in sub-health and pre-frailty states face increasing health risks that undermine quality of life. Home treatment devices offer a promising solution, but the key antecedent conditions and their configurational interactions remain unclear.MethodsThis study adopted a configurational approach to identify and analyze the key antecedent conditions influencing elderly users' satisfaction. Potential indicators were collected through an expanded snowballing literature review and refined using the Fuzzy Delphi Method (FDM) with 18 experts (June–July 2025), resulting in nine key conditions across four dimensions. A structured questionnaire was administered to 163 elderly respondents (aged 60–80) in Qingdao, China. Rough set analysis (RSA) was applied, with key configuration selection based on a coverage threshold of 10%.ResultsTen valid rules were obtained, revealing multiple causal pathways for both satisfaction and dissatisfaction. The dominant satisfaction pathway (Safety = 5 and Cost Control = 5) covered 45.37% of cases, whereas the main dissatisfaction pathway (Safety = 2 and Usefulness = 2) covered 35.71%. High safety and usefulness are key conditions, but their effects depend on combinations with cost, cultural, health, and policy-related conditions. Dissatisfaction, in contrast, is often triggered by low levels of basic conditions. These findings demonstrate causal complexity, equifinality, and asymmetry, extending configurational theory to the domain of home treatment devices and providing practical guidance for device design and policy development.